Analisis Aplikasi RRI Play Go Dalam Siaran Streaming Penyiaran Radio (Studi pada LPP RRI Palembang) - Maharini, Yuni; Hasmawati, Fifi; Manalullaili (Indonesian Journal Publisher, 2024)
Analysis Of The RRI Play Go Application in Streaming Radio Broadcacts (Study at LPP RRI Palembang) Mass media is a communication and information medium that disseminates information and can be accessed by the entire community en masse. One of the forms of mass media that is often found is radio, radio is a broadcast medium as a whole broadcast starting from material preparation, production, preparation of broadcast material, and broadcasting to reception of the broadcast or listeners in a place. There are many radio broadcasts in Indonesia, one of which is RRI (Radio Republik Indonesia), the development of information technology has meant that RRI does not only convey information from conventional radio networks, because RRI has released an application called RRI Play Go, this application provides information that is easily accessible anywhere. and at any time, actual and effective information. RRI Play Go is new media or digital media with the meaning of context media which has a combination of data, sound, text and various kinds of images stored in digital format. The RRI Play Go application has several features, namely, Programs, Music, Podcasts, News, Community, Partner Media and cctv Monitoring. The features available on the RRI Play Go application make all information and programs from various cities to remote areas easy to access, make it easier for users to find communities to build relationships, provide many music genres that can be accessed without time limits, access to news that is guaranteed without hoax and according to facts. The available categories also make it easier to find all the features according to your needs, podcasts with healthy and medical broadcasts, partner media that can be accessed easily and cctv monitoring that can be accessed anytime and anywhere.